2015
DOI: 10.1113/expphysiol.2014.079517
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of carotid body chemoreflex dysfunction during heart failure

Abstract: Recent advances have drawn interest in the potential for carotid body (CB) ablation or desensitization as an effective strategy for clinical treatment and management of cardio-respiratory diseases including hypertension, heart failure, diabetes mellitus, metabolic syndrome, and renal failure. These disease states have in common sympathetic overactivity, which plays an important role in the development and progression of the disease and is often associated with breathing dysregulation, which in turn likely medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 32 publications
2
56
0
2
Order By: Relevance
“…This finding raises the possibility that ROS-induced endothelial dysfunction could, via “stagnant hypoxia”, affect carotid chemosensitivity apart from the direct effects of ROS on glomus cell function. An analogous effect has been observed in an experimental model of heart failure (see Schultz (Schultz et al, 2015). Our laboratory has previously shown, in cerebral and skeletal muscle resistance arteries, that CIH impairs endothelium-dependent hypoxic vasodilation (Phillips et al, 2004).…”
Section: Discussionsupporting
confidence: 71%
“…This finding raises the possibility that ROS-induced endothelial dysfunction could, via “stagnant hypoxia”, affect carotid chemosensitivity apart from the direct effects of ROS on glomus cell function. An analogous effect has been observed in an experimental model of heart failure (see Schultz (Schultz et al, 2015). Our laboratory has previously shown, in cerebral and skeletal muscle resistance arteries, that CIH impairs endothelium-dependent hypoxic vasodilation (Phillips et al, 2004).…”
Section: Discussionsupporting
confidence: 71%
“…In turn, chemoreflex dysfunction contributes to sympathetic hyperactivity, hyperventilation and the associated breathing instability typically found in HFrEF subjects (Schultz et al, 2015). Accordingly, Di Vanna and collaborators demonstrated that the activity of muscle sympathetic nerves in response to central and peripheral chemoreceptor stimulation is exacerbated in patients with HFrEF (Di Vanna et al, 2007) (Table 1).…”
Section: Hyperadrenergic State In Heart Failurementioning
confidence: 99%
“…Oxidative stress is known to activate the carotid body in HF (Schultz et al, 2015). We now know that both circulating and local tissue levels of the pro-oxidant angiotensin II peptide are elevated in HF (Li et al, 2006).…”
Section: Hyperadrenergic State In Heart Failurementioning
confidence: 99%
“…Therefore, 5-HT and ET-1 may have a stronger effect on [Ca 2+ ] i in chronic hypoxia conditions and activate NSC to augment the chemosensitivity of glomus cells. Similar effects may occur in models of heart failure where the AngII and endothelin signaling is augmented, causing an enhanced CB chemoreflex (Schultz et al, 2015). …”
Section: Discussionmentioning
confidence: 74%